Implementation of Erlang C Formula in Inbound Call Center PT Telekomunikasi Selular - Rakhmatsyah, Nauravira Amalina (iora, 2024)
The use of services has become part of daily activities for humans. However, many users of services have been unable to fully utilize the services, resulting in complaints and requiring assistance. Call center as a service for providing information, technical support, and receiving complaints from service users are a solution to this problem. The large number of incoming calls from service users becomes a problem for service providers, so it is necessary to calculate the performance of the call center to implement the right number of agents. This research applies the Erlang C formula which is implemented in the inbound call center of PT Telekomunikasi Selular. Using data from November and December 2023 by reviewing several aspects, such as delay probability, service level, number of agents, and average delay time shows that the number of agents applied is sufficient, as seen from the service level that has met the desired target, so an increase in the number of agents is unnecessary.